Assessing the Link between Vessel Size and Maritime Supply Chain Sustainable Performance - Dariusz Bernacki (Energies, 2021)
This study determines the relationship between the increase in size of dry bulk carriers and container ships and the changes in sustainable shipping performance. It measures the elasticities of shipping costs for bulk carriers and container ships. Using regression, it derives the functions of the daily and unit costs of shipping with respect to the size of dry bulk carriers and container ships. The estimated daily and unit cost elasticities and cost models reveal significant but diversified impacts of vessel size on dry bulk and container shipping cost and its components, other operating capital, and fuel costs. Findings: Dry bulk carriers and containership size mean elasticities of daily operating costs estimates respectively: total operating costs 0.291 and 0.552, other operating cost (labor cost included) 0.238 and 0.328, capital costs 0.329 and 0.765, fuel costs 0.289 and 0.462; dry bulker and container ship unit shipping mean elasticity respectively: full operating costs (−0.751) and (−0.553), other operating cost (−0.804) and (−0.782), capital costs (−0.713) and (−0.399), fuel costs (–0.757) and (−0.702). This research provides an insight into the impact of technology and the way the services are provided (irregular versus regular) on shipping cost and energy savings. The cost models can be used for estimating the savings in shipping costs resulting from handling larger vessels in seaports.